Identificación de plantas nativas con fines ambientales en el sector de San Ignacio Parroquia Toacazo, periodo 2018. - Paste Broncano, Sandra Olimpia. (2018)
An ethnobotanical study of the native plants with environmental purposes was carried out in the community of San Ignacio, Toacazo parish, with the objective of identifying the knowledge that the inhabitants have regarding these plants. For this, a participatory action research was used and a structured interview was applied to obtain the information. The plants were collected, herborized and deposited in the herbarium of the Technical University of Cotopaxi (UTCE), the identification of the specimens was carried out in the PUCE. We identified 46 species with environmental purposes, belonging to 27 families, being the most representative: Asteraceae, Rosaceae, Butelaceae, Malvaceae and Scrophulariceae. The 7 most used species for these purposes were: Genista monspessulana (retamoaliso), Polylepis racemosa (yagual), Alnus acuminata (alder), Baccharis latifolia (black chilco), Lavatera arborea (mallow alborea), Ambrosia arborescens (frame), Buddleja incana (quishuar) The main function of these species based on the interviews was the use of curtains to break winds, barriers, shelter and shade. People with greater knowledge of the use of plants are in a range of 60 to 75 years, as age decreases, this knowledge is lost. Finally, a manual of the use of native plants for environmental purposes, illustrated and systematized, to help in the dissemination of them was systematized.